The role of mother tongue in teaching English to the first year students at Thai Nguyen University of Education - Đỗ, Thị Ngọc Phương (University of Languages and International Studies, 2017)
The use of mother tongue in foreign language teaching and learning has long been a controversial issue. However, as a common phenomenon in English language learning, the influence of mother tongue can not be ignored.